Senegal : Staff Report for the 2012 Article IV Consultation, Fourth Review Under the Policy Support Instrument, and Request for Modification of an Assessment Criterion-Staff Report; Staff Supplements; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation report for Senegal discusses the fourth review of the Policy Support Instrument (PSI) implementation and request for modification of an assessment criterion. Senegal's growth has been sluggish in recent years, with implications for poverty reduction. The authorities' policies since the last Article IV Consultation have been broadly in line with IMF recommendations. In the medium term, growth is expected to return gradually to about 5 percent a year. However, the economy remains exposed to substantial risks.